The impact of microbial mats in promoting record of Maastrichtian crocodylomorph tracks from Yacoraite Formation, Argentina - Martín, Alfredo Alejandro (2025)
Fil: Martín, Alfredo Alejandro. Instituto Superior de Correlación Geológica (INSUGEO, CONICET-UNT), Avenida Presidente Perón S/N, Tucumán, Tucumán Province 4107, Argentina